Quantification of a secondary task-specific tremor in a violinist after a temporal lobectomy - Lee, André; Tominaga, Kenta; Furuya, Shinichi; Miyazaki, Fumio; Altenmüller, Eckart (Frontiers in Human Neuroscience, 2014)
Task-specific tremors occur mainly during certain tasks and may be highly disabling. In this case study, we report on a 66-year-old violinist who developed a task-specific tremor of the right arm only while playing the violin four weeks after a temporal lobectomy, which had been performed as a result of his temporal lobe epilepsy. Since a similar case, to our knowledge, has not been reported so far, our aim was to quantitatively assess and describe the tremor by measuring (a) the electromyography (EMG) activity of the wrist flexor and extensor as well as (b) an accelerometer signal of the hand. We found a tremor-related frequency of about 7 Hz. Furthermore, at a similar frequency of about 7 Hz, there was coherence between the tremor acceleration and EMG-activity of the wrist flexor and extensor as well as between the tremor acceleration and coactivation. The tremorgenesis remains unclear, and possible explanations can only be speculative.